The Networked Smart Gadgets and Their Role(s) in Enhancing Learning Autonomy in Higher Education’s EFL Context - Hamda Abdulaziz Laouini (ELT Worldwide: Journal of English Language Teaching, 2021)
The present study explores the perceptions of EFL teachers in higher education on the role of handheld networked devices in promoting autonomous learning. In this project 43 male teachers from King Abdulaziz University (KAU) and the University of Jeddah (UJ) in Saudi Arabia (KSA) responded to a survey. Qualitative data, on the other hand, was gathered through a silent interview where informants answered five open-ended questions related to study’s research questions. The findings revealed the participants value the usefulness of smartphones in enhancing autonomy in language learning. They were also of the view that smartphones have beneficial characteristics when used in actual classroom. In addition, the results show that most of the participants are for a purposeful and guided integration of this type of technology in order to help learners develop the required linguistic and extra-linguistic skills. Equally important was the finding that use the of smartphones along well-developed L2 learning applications in language learning cannot replace the teachers’ vital and crucial role in the whole learning process.